A Semantic Analysis of Language used in Disaster Announcements and Signages in Davao City - Cabunoc, Mikhaila Elaine C.; NGO, CRISTY GRACE; Baer , Madelon Vi M.; Sampiano, Mairaleen I. (Journal Corner of Education, Linguistics, and Literature, 2024)
This qualitative corpus-based study aimed to identify the elements in semantic as well as analyze the relationship between an entity and its neighboring non-entity text found in disaster announcements and signages in Davao City. The study utilized social media and public signages as means of collecting data wherein disaster announcements and signages related to flood, fire, and earthquake are being focused. To analyze the data, the researchers used two parts of the process of semantic analysis namely Lexical Semantic Analysis focusing on elements in semantic and Relationship Extraction centralizing on entities and relations. The results exhibit that in those announcements and signages six (6) elements in semantics were commonly found namely Homonyms, Hypernyms, Hyponyms, Polysemy, Synonymy, and Antonymy in which each conveys different lexical meanings that affects the meaning of a sentence. Furthermore, a category of relations was found in the extraction process of the entity and non-entity text which are Description, Causation, Mitigation, Preparedness, and Response. These categories helped explain how each relationship formed with an entity can provide different meaning and different context. All things considered, copywriters of public service announcements for disaster announcements and signages should take note of the word choice and their arrangement and linkage when writing so as to have a better communication and understanding with the citizens to avoid vulnerability with risks.